Beautiful minds : the parallel lives of great apes and dolphins - Bearzi, Maddalena (Harvard University Press, 2008)
In this first book to study apes and dolphins side by side, a dolphin biologist and a primatologist who have spent their careers studying these animals in the wild, combine their insights with compelling results. Beautiful Minds explains how and why apes and dolphins are so distantly related yet so cognitively alike and what this teaches us about another large-brained mammal: Homo sapiens.